Transparansi dalam Komunikasi Public Relations: Analisis Kasus Penolakan Tawaran Buzzer Oleh Jerome Polin - Aisyah Wigayati; Wahid Restu Nadyani; Akbar Bagas Kurniawan; Marjam Desma Rahadhini (ALAMTARA, 2025)
This article discusses the significance of transparency in public relations communication through a case study of Jerome Polin, a well-known Indonesian content creator who publicly refused a government offer to act as a paid “buzzer” for IDR 150 million. This research aims to analyze how transparency serves as an ethical communication practice and a strategic approach to building public trust in the digital era. The study employs a qualitative descriptive method using a case study approach, with data collected from online news portals and social media posts by Jerome Polin between August and October 2025. The results show that transparent communication enhances personal credibility, encourages public dialogue on ethical issues, and fosters media literacy about opinion manipulation. However, transparency also brings challenges, such as public skepticism toward evidence authenticity and accusations of self-promotion. The study concludes that transparency, when combined with accountability and two-way communication, strengthens credibility and public trust while countering manipulative communication practices. Recommendations for standards and openness in public relations to maintain integrity and long-term reputation in digital communication.